Digital Ritual: Police–Public Social Media Encounters and ‘Authentic’ Interaction - Henry, Alistair (The British journal of criminology, 2024)
This article formulates the concept of digital ritual to characterize the continuum of symbolic encounters enabled by social media affordances, and to explain their solidarity-enhancing potential. Applying digital ritual to police uses of social media confirms this promise but also reveals risks of mediated authenticity. The article cautions against influencer styles of engagement that risk privileging popularity over probity in ways dangerous for police legitimacy. It is argued that insights from conceptualizing online encounters as digital rituals can instead be marshalled to support an alternative ‘working personality of the digital cop’; one reflecting principles of candour and democratic policing that provide a sounder basis for establishing what ‘authentic’ online police-public interactions ought to look like.